Bioinformatic Dissecting of TP53 Regulation Pathway Underlying Butyrate-induced Histone Modification in Epigenetic Regulation. (January 2014) - Li, Cong-Jun; Li, Robert W.
Butyrate affects cell proliferation, differentiation, and motility. Butyrate inhibits histone deacetylase (HDAC) activities and induces cell-cycle arrest and apoptosis. TP53 is one of the most active upstream regulators discovered by ingenuity pathways analysis (IPA) in our RNA-sequencing data set. TP53 signaling pathway plays key role in many cellular processes. TP53 pathway and their involvement in cellular functions modified by butyrate treatment were scrutinized in this report by data mining the RNA-sequencing data using IPA (Ingenuity System ® ). The TP53 mechanistic pathway targets more than 600 genes. Downstream analysis predicted the activation of the TP53 pathway after butyrate treatment. The data mining also revealed that nine transcription factors are downstream regulators in TP53 signaling pathways. The analysis results also indicated that butyrate not only inhibits the HDAC activities, but also regulates genes encoding the HDAC enzymes through modification of histones and epigenomic landscape.